Epidemiologic significance of Toxoplasma gondii infections in turkeys, ducks, ratites and other wild birds: 2009–2020. Issue 1 (19th January 2021) - Dubey, J. P.; Murata, F. H. A.; Cerqueira-Cézar, C. K.; Kwok, O. C. H.; Su, C.
Abstract: Toxoplasma gondii infections are common in humans and animals worldwide. Wild and domestic avian species are important in the epidemiology of T. gondii infections because felids prey on them and excrete millions of oocysts in the environment, disseminating the infection. Herbivorous birds are also excellent sentinels of environmental contamination with T. gondii oocysts because they feed on the ground. Toxoplasma gondii infections in birds of prey reflect infections in intermediate hosts. Humans can become infected by consuming undercooked avian tissues. Here, the authors reviewed prevalence, persistence of infection, clinical disease, epidemiology and genetic diversity of T. gondii strains isolated from turkeys, geese, ducks, ratites and avian species (excluding chickens) worldwide 2009–2020. Genetic diversity of 102 T. gondii DNA samples isolated worldwide is discussed. The role of migratory birds in dissemination of T. gondii infection is discussed.